THE FEATHER’S DIAGNOSTIC FEATURES OF GALLIFORMES - O. Chernova; O. Silaeva; T. Perfilova (Теория и практика судебной экспертизы, 2014)
Microstructure of the contour feathers (remex and covert) of 9 species has been compared:Bonasa bonasia, Tetrao urogallus, Lagopus lagopus, Lyrurus tetrix, Coturnix coturnix,Perdix perdix, Francolinus francolinus, Phasianus colchichus, Gallus gallus domesticus.Feathers (one remige and one covert feather) from 3–15 specimens of each specieshave been studied. It is shown, that the length of a wing varies considerably, positivelycorrelating with the size of birds.